Climate characteristics of dust aerosol and its transport in major global dust source regions. (1st November 2020) - Xiong, Jie; Zhao, Tianliang; Bai, Yongqing; Liu, Yu; Han, Yongxiang; Guo, Chunwei
Abstract: In this paper, a 20-year (1991–2010) simulation of dust aerosol emission is conducted by using the global climate model CAM 5.1 (Community Atmosphere Model, version 5.1). The simulation results revealed that North Africa, the Arabian Peninsula and the Middle East, East Asia, Australia, and the other regions respectively account for 60%, 18%, 12%, 2.5% and 7.5% of the global dust aerosol emission. On this basis, the climatology of dust aerosol emission, deposition and transport in the major dust source regions of the world are characterized. The results show that the inter-annual trends of dust emissions and depositions in the four major source areas are basically consistent, and the seasonal variations of dust emissions, dry and wet depositions are stronger than inter-annual variations. The seasonal variations of emissions and total depositions are the strongest in East Asia and the weakest in North Africa. The strongest seasonal variation of wet deposition appears in North Africa and the weakest in Australia. The dry and wet deposition ratios vary significantly with season. East Asia is dominated by wet deposition, while other areas are dominated by dry deposition. The dust transport in four major dust regions is mainly affected by the circulation systems at each level, the free tropospheric (500 hPa) transport of dust aerosol is controlled by the mid-latitude westerlies, and the dust aerosol is predominantly transported from west to east. But, the transport of dust aerosols in the atmospheric boundary layer shows distinct regional characteristics, with weak inter-annual variation and strong seasonal variation. Highlights: A 20-year (1991–2010) simulation of dust aerosol is conducted by using the global climate model CAM 5.1. The simulation results revealed that North Africa, the Arabian Peninsula and the Middle East, East Asia, Australia are four major dust source regions, the climatology of dust aerosol emission, deposition and transport in the major dust source regions of the world are characterized. The dust transport in four major dust regions is mainly affected by the circulation systems at each level.